Multi-modality organ-based approach to expected imaging findings, complications and recurrent tumour in the genitourinary tract after radiotherapy - Schieda, Nicola (Springer Berlin Heidelberg, 2013)
PURPOSE: Radiotherapy (RT) is an integral component in the management of many abdominal and pelvic malignancies. Imaging follow-up in patients who have received RT is performed to assess for treatment response, evaluate for tumour recurrence and to diagnose complications related to treatment. The purpose of this pictorial review is to depict the expected imaging findings and potential complications following RT in the genitourinary (GU) tract using an organ-based approach and to review the diagnosis of locally recurrent tumour in the GU tract following RT. CONCLUSIONS: Some GU malignancies, namely cervical and prostatic carcinoma, can be treated with radical RT with intent to cure. More frequently, the GU tract is indirectly treated as a result of RT to adjacent cancers. Expected imaging findings, RT-related complications and the diagnosis of recurrent tumour following RT in the GU tract often necessitate a multi-modality imaging approach, the incorporation of functional imaging techniques and an organ-based approach for diagnosis.